The Effectiveness of Reflection E-Portfolio in English Language Learning Based on Deep Learning and Case-Based Learning - Santoso, Yan Imam; Sugiharto, Prasetyawan Aji; Putri, Rosalidya; Wibisana, Mohammad Andre (Proceeding International Conference on Education, 2025)
This study investigates the effectiveness of integrating case-based learning (CBL) and deep learning (DL) with the use of reflection e-portfolios in English language learning. The research is framed within the context of 21st-century education, emphasising the development of critical thinking, creativity, collaboration, and communication (4Cs). A qualitative method with a phenomenological approach was employed to explore teachers’ perceptions and experiences. Data were collected through focus group discussions (FGDs), surveys, and in-depth interviews involving 20 English teachers at the senior high school, vocational school, and Islamic senior high school levels in Kendal Regency. The findings reveal that while most teachers are relatively familiar with CBL—often equating it with problem-based learning—DL remains a new and less understood approach, thereby requiring further training and support. Teachers acknowledged that both approaches present challenges, particularly in terms of time allocation, creativity, and technical implementation. Nevertheless, reflection e-portfolios were perceived as a valuable evaluation tool that fosters objectivity, transparency, and openness in monitoring student progress. They allow teachers, students, and even parents to engage in the learning process more effectively. Overall, the integration of CBL, DL, and reflection e-portfolios was found to enhance students’ motivation and support the development of the four language skills (listening, speaking, reading, and writing) as well as the 4Cs. This study concludes that such integration offers a sustainable innovation for improving the quality of English language learning while simultaneously addressing the challenges of 21st-century education.